Personal income distribution in Turkey: A generalized ordered logit analysis - Vedat Kaya; Ali Kemal Çelik; Muhammet Kutlu (Economic Journal of Emerging Markets, 2020)
Income distribution decomposition may be affected by a variety of different factors. The main objective of this study is to examine potential factors of personal income distribution in TRA1 sub-region, the three highest income inequality in Turkey. The dataset was drawn from the Turkish Household Income and Life Conditions Survey. Due to the natural ordering of the dependent variable, a generalized ordered logit model was performed to analyze the data. Findings/Originality: The estimation results reveal that gender, age, marital status, educational level, occupational group, and general health status were found to be statistically significant determinants of personal income distribution in TRA1 sub-region of Turkey. The empirical evidence gathered from this study may add an explanation for personal income distribution decomposition in sub-regions of Turkey. In addition, the finding contributes to the human capital theory development that implies the importance of educational policy as one of the effective tools in reducing inequality.